A typology of integrated care policies in the care home sector: A policy document analysis - Simpson, Glenn; Entwistle, Charlotte; Short, Andrea D.; Morciano, Marcello; Stokes, Jonathan (Frontiers in Public Health, 2023)
Background Health and social care systems in many countries have begun to trial and adopt “integrated” approaches. Yet, the significant role care homes play within the health and social care system is often understated. A key first step to identifying the care home integration interventions that are most (cost-)effective is the ability to precisely identify and record what has been implemented, where, and when – a ‘policy map’. Methods To address gaps relating to the identification and recording of (cost-)effective integrated care home interventions, we developed a new typology tool. We conducted a policy mapping exercise in a devolved region of England – Greater Manchester (GM). Specifically, we carried out systematic policy documentary searches and extracted a range of qualitative data relating to integrated health and social care initiatives in the GM region for care homes. The data were then classified according to existing national ambitions for England as well as a generic health systems framework to illustrate gaps in existing recording tools and to iteratively develop a novel approach. Results A combined total of 124 policy documents were identified and screened, in which 131 specific care home integration initiatives were identified. Current initiatives emphasised monitoring quality in care homes, workforce training, and service delivery changes (such as multidisciplinary teams). There was comparatively little emphasis on financing or other incentive changes to stimulate provider behaviour for the care home setting. We present a novel typology for capturing and comparing care home integration policy initiatives, largely conceptualising which part of the system or specific transition point the care home integration is targeting, or whether there is a broader cross-cutting system intervention being enacted, such as digital or financial interventions. Conclusions Our typology builds on the gaps in current frameworks, including previous lack of specificity to care homes and lack of adaptability to new and evolving initiatives internationally. It could provide a useful tool for policymakers to identify gaps in the implementation of initiatives within their own areas, while also allowing researchers to evaluate what works most effectively and efficiently in future research based on a comprehensive policy map.